Privatización de bienes comunales y despojo campesino en la Extremadura española, siglos XIX-XX - Sergio Riesco Roche (Ler História)
The institutional study of the “commons” provides a lens for understanding the transformation of peasant societies during the construction and consolidation of the liberal state. From the late 18th century through much of the 20th century, there was a massive dismantling of this communal property system, which had a profound social impact. This paper focuses on the case of Extremadura, a region in southwestern Europe. The unique geographic and environmental conditions of this area influenced the process of dismantling the commons. The institutional framework and the mechanisms used to carry out this destruction are examined within the broader context of modernization in the agricultural sector. Additionally, this study highlights the different forms of resistance to these changes and the attempts to restore the commons, both of which coincide with Spain's two republican periods, before the topic disappeared from public debate following the end of the Civil War.